Formation of buckling resistance in a transfemoral prosthesis - G. N. Burov; O. L. Belyanin; M. V. Chernikova; V. A. Bol'shakov; A. S. Drobakha (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Introduction. The principles of construction of the knee joint in the transfemoral prosthesis are considered. The design of the knee joint in the transfemoral prosthesis with an original mechanism for ensuring buckling resistance in the prosthesis is proposed. Goal. Create an artificial knee joint, which provides a reliable mechanism of strut stability during walking by quickly blocking the flexion-extension of the artificial knee joint in the prosthetics for high amputations of the lower extremities when resting on the prosthesis. Materials and methods. One of the main problems that exist in the development of knee joints in a femoral prosthesis is the presence in the design of the module of a mechanism that ensures its blocking from bending when walking at the moment of support of the prosthesis in the transfer phase of a healthy limb. In the knee joints of various companies, this issue is solved in different ways. For example, some simple singleaxis knee joints are designed to lock when the disabled person is in a standing position. Walking is carried out without flexion in the knee joint. To unlock, pull the cable (transition to a sitting position). In some single-axis hinges, a locking function is applied using the weight of a disabled person. In the phase of support on a full foot, the hinge closes due to the weight load on it and opens by transferring weight to the toe. In more complex multi-axis module designs, there is a so-called geometric lock. The closure in the stance phase occurs due to the correct arrangement of the axes relative to each other. The opening occurs in the transfer phase. The object of the study. The mechanisms of the knee joint, which provide a handicapped person's resistance to buckling while walking on a transfemoral prosthesis. The subject of the study. The design of the knee joint, which provides self-braking due to a coupling with a split disc. Results. The study made it possible to substantiate the practical possibility of creating a knee joint of prosthetics for high amputation with a braking device made in the form of a split disc clutch. Discussion. Currently, there are various designs of knee joint that have mechanisms of buckling. When considering modern knee joint of well-known manufacturers, the main ways of ensuring buckling resistance are determined. The polycentric knee module of the company "Ossur" implements the principle of knee locking due to the displacement of the instantaneous axis when the knee is extended, thereby providing buckling resistance. In the Ottobock knee joint, the knee axis is automatically closed under the influence of human weight. Domestic manufacturers of knee modules are ORTHOS (Novosibirsk) and Metiz. Also, the scientific and production corporation "Precision Instrument Engineering Systems" (NPC SPP, part of Roscosmos) announced the production of the knee module "Aktiv-2". Due to the restriction of imports of foreign products, state prosthetic and orthopedic enterprises are interested in the development and production of domestic prosthetic and orthopedic products, including artificial knee joints of various designs. Conclusions. The principles of constructing the design of the knee joint of the above knee prosthesis have been formed.